Ethnic Variation in the Manifestation of Parkinson’s Disease: A Narrative Review - Ben-Joseph, Aaron (J Parkinsons Dis, 2020)
The global prevalence of Parkinson’s disease is increasing, yet the characteristics, risk factors and genetics of PD in Black, Asian and Hispanic populations is little understood. In this paper we review the published literature on clinical variation in the symptoms and signs of Parkinson’s disease in different ethnic groups and responses to treatment. We included any study that sampled patients with Parkinson’s disease from distinct ethnic backgrounds. We conclude that whilst there is little published evidence for ethnic variation in the clinical features of Parkinson’s disease, there are substantial limitations and gaps in the current literature, which mean that the evidence does necessarily not fit with clinical observation. Possible explanations for expected differences in manifestation include genetic determinants, the co-existence of cerebrovascular disease and/or Alzheimer’s disease pathology, healthcare inequalities and socio-cultural factors.